2008
DOI: 10.1097/nmd.0b013e31818132a3
|View full text |Cite
|
Sign up to set email alerts
|

Latent Class Analysis of Delusion-Proneness

Abstract: Latent class analysis (LCA) has emerged as the best suitable statistical tool to identify separate dimensions (latent classes) when analyzing dichotomous data; its objective is to categorize people into classes using the observed items and to identify those items that best distinguish between classes. LCA was applied to the Peters et al. delusions inventory, an inventory in a dichotomous format (Yes/No) aimed at investigating proneness to delusion in the general population. The study involved 82 patients diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…In either case, our findings suggest questions of grandiosity may be less specific for evaluating the psychosis risk. The symptom clusters found in our study shares some similarities with that reported by Rocchi et al (40), where latent class analysis was applied to a delusions inventory. Although only delusional symptoms were analyzed, these authors identified four classes including a prominent grandiosity/hypomania class.…”
Section: Discussionsupporting
confidence: 89%
“…In either case, our findings suggest questions of grandiosity may be less specific for evaluating the psychosis risk. The symptom clusters found in our study shares some similarities with that reported by Rocchi et al (40), where latent class analysis was applied to a delusions inventory. Although only delusional symptoms were analyzed, these authors identified four classes including a prominent grandiosity/hypomania class.…”
Section: Discussionsupporting
confidence: 89%
“…The general pattern of odd beliefs and odd perceptions marking a single factor is unsurprising, given the consistently high relations between measures of oddities of perception and belief (rs = .50 to .79) (Bentall, Claridge, & Slade, 1989;Berenbaum et al, 2006;Brown, Silva, Myin-Germeys, Lewandowski, & Kwapil, 2008;Fonseca-Pedrero et al, 2009;Kelley & Coursey, 1992;Kendler & Hewitt, 1992;Kerns, 2006;Kwapil et al, 2008;Lewandowski et al, 2006;MacDonald, Pogue-Geile, Debski, & Manuck, 2001;Mohanty et al, 2008;Ross, Lutz, & Bailley, 2002;Stringer et al, 2010;Yon, Loas, & Monestes, 2009).…”
Section: Schizotypy: Structurementioning
confidence: 99%
“…Scales that are saturated with aesthetic appreciation content (e.g., self-reported intellectual and cultural interests) are only modestly (i.e., r < .30; Bryson, Grimshaw, & Wilson, 2009;G. M. Grimshaw, personal communication, July 2, 2010;Kwapil, Wrobel & Pope, 2002) to moderately (i.e., r = .30 to .40; G. Miller & Tal, 2007;Rawlings, 2000;Ross et al, 2002) related to schizotypy and dissociation. In contrast, the CEQ is moderately to strongly (r = .44 to .67) related to dissociation and schizotypy see Merkelbach et al, 2001 for a summary of older findings of this relation; Merkelbach, Campo, Hardy, Giesbrecht, 2005;Merkelbach, Horselenberg, & Schmidt, 2002;Merkelbach & Jelicic, 2004;Merkelbach, Muris, & Rassin, 1999;Merkelbach, Muris, Horselenberg, & Stougie, 2000;Murray, Fox, & Pettifer, 2007;Pekala, Angelini, & Kumar, 2001;Sanchez-Bernardos & Avia, 2006;van de Ven & Merkelbach, 2003).…”
Section: Boundariesmentioning
confidence: 99%
See 2 more Smart Citations